1998
DOI: 10.1046/j.1365-2141.1998.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose aspirin does not lower in vivo platelet activation in healthy smokers

Abstract: Smoking causes atherosclerosis, and smokers have increased thromboxane (TXA2) formation. As aspirin inhibits TXA2 production we speculated that smokers would preferentially profit from inhibition of the TXA2 pathway by aspirin. Increased expression of P-selectin, a constituent of the alpha-granules of platelets, and increased levels of circulating (c)P-selectin in plasma are markers for platelet activation. The aim of this study was to compare P-selectin expression on platelets between smokers and nonsmokers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 12 publications
1
36
0
1
Order By: Relevance
“…4,5,11 Activated platelets accumulating in thrombi at the site of ruptured atherosclerotic plaques will express CD62P. In clinical studies, P-selectin has been shown to be a marker of platelet activation related to adverse cardiovascular events such as hypertension, coronary artery disease, cerebrovascular disease, and peripheral arterial disease, 6,7,[10][11][12] and also to be a predictor of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5,11 Activated platelets accumulating in thrombi at the site of ruptured atherosclerotic plaques will express CD62P. In clinical studies, P-selectin has been shown to be a marker of platelet activation related to adverse cardiovascular events such as hypertension, coronary artery disease, cerebrovascular disease, and peripheral arterial disease, 6,7,[10][11][12] and also to be a predictor of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, platelet activation can be detected directly by measuring surface antigen CD62P using flow cytometry. 2,3,5,9,10,12 Furthermore, detection of platelet-neutrophil complexes (PNC), which are formed as a result of interaction with CD62P provides an additional means to detect platelet activation. 24 The purpose of this study was to investigate the association between arterial stiffness and platelet activation by measuring PWV, P-selectin, and PNC in subjects without atherosclerotic disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets contribute pivotally to atherothrombotic disease such as myocardial infarction and stroke; there-epinephrine in whole blood and platelet-rich plasma than in men 16) . Smoking is a common environmental factor that increases platelet function 17,18) . In the context of this research, population-based research is helpful in providing information on the confounding factors for platelet responsiveness to agonists; however, these studies are very limited due to the difficulty of platelet aggregability measurement in a community setting.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that aspirin exerts its antithrombotic effect by inhibiting platelet aggregation, and many studies have demonstrated the absence of any effect of aspirin on platelet activation. 21,22 Also, increased platelet activation, despite aspirin treatment, has been shown in many prothrombotic disorders. 23,24 No studies to date have determined the most appropriate antithrombotic treatment after transcatheter closure of PFO, and the choice of antithrombotic treatment after this procedure has been empirically determined, with aspirin the therapy most frequently used in these cases.…”
Section: Discussionmentioning
confidence: 99%